First alcohol treatment institutions in today's Czech Republic and Slovak Republic - Šejvl, Jaroslav; Gavurová, Beáta; Barták, Miroslav; Mašlániová, Miroslava; Miovský, Michal (Central European Journal of Public Health, 2019)
OBJECTIVE: Drawing on qualitative analysis of selected historical documents, the paper seeks to provide a definition of the general characteristics of the first institutional alcohol treatment facilities in today's Czech Republic and Slovakia, taking into account the historical context of the first half of the 20th century. An additional aim was to point out the importance of archival research and its contribution to understand the determinants of alcohol-related agenda and alcohol treatment. METHODS: The basic data platform was generated by analysis of historical documents pertaining to the subject matter under study and to institutional processes in different periods. The data was processed using the open coding method (as part of the grounded theory approach) and other specific methods based on the matching of data from scientific and professional literature and archives in different periods. Over 1,100 pages of text from relevant archival materials were analysed. This research is original, no such systematic analysis of historical documents on this subject matter has been conducted on such a scale with the intention of identifying the general correlates of the historical development of an alcohol-related agenda and alcohol treatment. RESULTS: The establishment of the first institutional facilities intended to provide treatment for alcohol dependency was based on the notion of addiction as a disease, which needs to be treated in dedicated facilities applying an individualised approach. The circumstances of the establishment of the facilities under analysis were similar. Their existence was made possible by distinguished personalities rather than a general belief and social pressure that the issue of alcohol addiction should be addressed. This also explains the fact that the occupancy of these facilities never reached their full capacity, that they were not self-reliant in economic terms, and that they did not readily resume their operation after 1945. CONCLUSIONS: The analysis of the establishment, operation, and dissolution of these facilities at the time reveals the discontinuity in the approach to alcohol abuse and its treatment in the context of the historical development and perception of alcohol-related problems in Czech and Slovak society in the first half of the 20th century. Significant social changes occurred after 1948. New legislative instruments were used to enforce treatment based on a principle that was different from the previous approaches. The results of our study also make it possible to reveal the intensity of apparent individual and institutional motives in the process of the development of alcohol treatment in historical terms and its projection into different post-war periods. The understanding of these correlates will help in designing additional trajectories of research into the effects of social and political changes on addiction treatment and thus identifying the intensity of the historical development and its influence on the perception of addiction treatment at present. These findings will also be of great importance for a historical comparative analysis, including overlaps with the development of recent theories, and will support the emergence of new areas of study for the social sciences.
Keywords: History, 20th Century; dějiny 20. století; alkoholismus; Slovenská republika; Česká republika; lidé; Slovakia; Czech Republic; Substance Abuse Treatment Centers; centra pro terapii drogových závislostí; Qualitative Research; Alcoholism; kvalitativní výzkum; Humans